The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1249/mss.0000000000002133
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water-based Exercise Training in People with Type 2 Diabetes

Abstract: Purpose: To investigate the effects of 8 weeks of upright water-based exercise training in people with type 2 diabetes.Methods: Thirteen participants with type 2 diabetes (54% male; 60.9 ± 9.6 years, mean ± standard deviation) completed eight weeks of upright water-based exercise training at a moderate intensity (60-80% of exercise test-derived maximum heart rate), for one hour, three times a week (TG). Fourteen participants (64% male; 63.9 ± 9.8 years) acted as a control group (CG) who maintained their usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
(49 reference statements)
3
19
0
Order By: Relevance
“…Out of the 29 included studies, three articles (95 patients) [28,49,53] demonstrated that structured physical exercise interventions were associated with an increase of 17.97 kg in the strength measures of lower limb muscle evaluated by 1RM of leg-press (95% CI 4.08% to 31.87%; I 2 0%; p for heterogeneity = 0.62) as compared with control (Figure 3).…”
Section: Lower Limb Muscle Strengthmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 29 included studies, three articles (95 patients) [28,49,53] demonstrated that structured physical exercise interventions were associated with an increase of 17.97 kg in the strength measures of lower limb muscle evaluated by 1RM of leg-press (95% CI 4.08% to 31.87%; I 2 0%; p for heterogeneity = 0.62) as compared with control (Figure 3).…”
Section: Lower Limb Muscle Strengthmentioning
confidence: 99%
“…The last two studies were transformed to mL/kg•min using the body weight presented by each of the studies. The other eight studies [31,40,42,45,46,[51][52][53] had the measure of oxygen consumption in VO 2peak and all of them with the unit of measure in mL/kg•min. The results of VO 2max and VO 2peak were combined in the same meta-analysis.…”
Section: Physical Fitnessmentioning
confidence: 99%
See 3 more Smart Citations